Effect of Subvalvular Changes on Mitral Valve Leaflets Excursion after Percutaneous Transvenous Mitral Commissurotomy (Cardiovascular Journal, 2015)
Background: Aim of our study was to predict the effect of subvalvular changes on mitral valve leaflets excursion in a patient with mitral stenosis following percutaneous trans-venous mitral commissurotomy.Methods: Total of 60 patients of severe mitral stenosis were enrolled in the study. Transthoracic echocardiography was done on the day before percutaneous trans-venous mitral commissurotomy and 24-48 hours after percutaneous trans-venous mitral commissurotomy. Subvalvular area, anterior and posterior leaflets excursion were recorded.Results: Following percutaneous trans-venous mitral commissurotomy there were significant increase in anterior leaflet excursion from 1.8 ± 0.2 to 2.2 ± 0.2cm (p=